Optimization of micro and macro economic empowerment within the framework of Islamic economics: An integrative study - Mohamad Ghozali; Mohamad Anton Athoillah (Journal of Enterprise and Development (JED), 2023)
Purpose — This research aims to analyze micro and macro-economic empowerment within the Islamic economic framework, specifically in Indonesia. The study discusses the fundamental principles of economic empowerment in Islam and highlights the role of both micro and macro aspects in establishing a resilient and sustainable economic structure.Method — This study conducts a literature review to gather, analyze, and synthesize relevant literature sources on the research topic. Various sources such as journal articles, books, reports, theses, and policy documents are searched using academic databases like Google Scholar, Springer, Science Direct, and Scopus. The review involves critically assessing research methodology, findings, and conclusions, and identifying major themes in the literature.Result — This research identifies key barriers such as limited understanding and awareness, underdeveloped infrastructure, and a lack of diverse and innovative financial products. The proposed solutions and strategies include improving Islamic economic education and literacy, developing a broader array of innovative financial products, enhancing infrastructure, and establishing supportive policies and regulations. This study asserts that an economic empowerment strategy in line with Islamic principles can significantly contribute to Indonesia's economic development and foster financial inclusion as well as socio-economic justice.Contribution — This research offers fresh insights into micro and macro-economic empowerment within the Islamic economic framework, with a specific focus on the Indonesian context. The study explicitly integrates micro and macro aspects, which has been rare in previous research, and reveals how these two facets interact and contribute to sustainable economic development.